Electromagnetic modes of a coaxial plasma waveguide in an external magnetic field - Karas, I.V.; Zagrebelny, I.A. (Вопросы атомной науки и техники, 2015)
For carrying out of the further numerical comparisons with experimental researches on breakdown of a mixture of gases by microwave radiation with a stoсhastic jumping phase the theoretical researches of wave dispersive properties of the coaxial waveguide are carried out. Electromagnetic modes of a coaxial plasma waveguide in an external magnetic field are investigated. The existence of quasi-TEM modes in a finite-strength magnetic field is demonstrated. It is shown that, in the limits of infinitely strong and zero magnetic fields, this mode transforms into a true TEM mode.